Molecular docking, pharmacophore modelling, MD simulation and in silico ADMET study reveals bitter cola constituents as potential inhibitors of SARS-CoV-2 main protease and RNA dependent-RNA polymerase. Issue 4 (4th March 2023) - Oluyori, Abimbola Peter; Olanipekun, Bolatito Eunice; Adeyemi, Oluyomi Stephen; Egharevba, Godshelp Osas; Adegboyega, Abayomi Emmanuel; Oladeji, Oluwole Solomon
Abstract: A mini survey was employed in the search of herbs and spices which people believe could prevent them from contracting COVID-19. Phytochemicals which have been earlier implicated for the bioactivity of the afore-mentioned herbs and spices were identified through literature search. The phytochemicals were then subjected to pharmacore modelling, molecular docking and molecular dynamics simulation in order to identify phytochemicals that could serve as inhibitors of 3-Chymotryprin-like protease and RNA dependent–RNA polymerase of SARS-CoV-2. The drug-likeness and toxicity profile of the phytochemicals were afterwards predicted via ADMET studies. The mini survey showed ginger, garlic, bitter cola, as the lead-herbs which could find application in anti- COVID-19 therapy. Literature search revealed 27 phytochemicals were implicated for bioactivity of these herbs. Of these 27 phytoconstituents that were docked with 3-chymotrypsin-like protease and RNA dependent–RNA polymerase, the constituents of bitter cola had lower docking scores than other phytochemicals. MD simulation results showed that Garcinia biflavonoid I displayed less comformational changes and the better binding free energy. Also, the garcinia biflavonoids had relatively safe ADMET predictions. Hence, Garcinia biflavonoids and some other constituents of bitter cola could be further modified so as to obtain safe pharmaceutical intervention for the COVID-19 challenge. Communicated by Ramaswamy H. Sarma